Numerical Investigation of Electronic Cooling with Phase Change Material - Medhi, Nur Syafiqah (IRC, 2018)

(untitled)
This research numerically investigates the employment of phase change material (PCM) with liquid cooling channels of different geometry on microprocessor cooling using a computational fluid dynamics approach. The objective of the study is to investigate the thermal performance of cooling channel with phase change material for microprocessor cooling. The liquid cooling channel geometry investigated are parallel and serpentine while the PCM is tricosane. Parametric analysis on liquid cooling channels with and without PCM was conducted. Laminar Newtonian fluid flow is assumed for the numerical study. A mesh independence study was carried out and a grid size of 4x10-4 elements was found to be sufficient for the numerical investigation purposes. The cooling channels were tested at two different Reynold’s number; Re 400 and Re 800. Evidently, at higher Reynold’s number, the convective heat transfer is better, due to the higher flow velocity. The hybrid cooling channel with PCM has shown promising results, yielding lower average temperatures than without PCM. The effect of PCM thickness was also studied. 5mm thick PCM resulted in further reduction in temperature from the 1mm thick PCM. The serpentine channel’s maximum average separator temperature was 358.5 K while the parallel channel’s was 378.9 K, which is a reduction of 7 K and 14.67 K respectively.